Photocatalytic Generation of π-Allyltitanium Complexes from Butadiene via a Radical Strategy - Li, Fusheng; Lin, Shuangjie; Li, Xiyu; Shi, Lei (Synthesis, 2021)
The direct conversion of industrial feedstock chemicals into highly valuable fine chemical intermediates is of great appeal to the synthetic community as well as industrial applications. This study reports a conceptually new radical strategy for the photocatalytic generation of π-allyltitanium complexes from butadiene. This novel and environmentally benign strategy enables the direct three-component allylation of carbonyls with 1,3-butadiene and α-bromocarboxylates, providing rapid access to valuable homoallylic alcohols with exceptional regio- and diastereoselectivity control.
Keywords: photocatalysis; allylation; radical; butadiene; π-allyltitanium